Vitamin D3 enhances the response to cisplatin in bladder cancer through VDR and TAp73 signaling crosstalk. (10th April 2019) - Bunch, Brittany L.; Ma, Yingyu; Attwood, Kristopher; Amable, Lauren; Luo, Wei; Morrison, Carl; Guru, Khurshid A.; Woloszynska‐Read, Anna; Hershberger, Pamela A.; Trump, Donald L.; Johnson, Candace S.
Abstract: Background: Vitamin D3 (VitD) deficiency is linked to increased incidence and worse survival in bladder cancer (BCa). In addition to cystectomy, patients are treated with cisplatin‐based chemotherapy, however 30%‐50% of patients do not benefit from this treatment. The effects of VitD deficiency on response to chemotherapy remain unknown. Methods: To test effects of VitD supplementation on the response to cisplatin we analyzed patient serum VitD levels and correlated that with survival. In vivo, VitD deficient mice were treated with cisplatin, with or without pretreatment with the active VitD metabolite, 1, 25 dihydroxyvitamin D3 (1, 25D3 ). Lastly, using BCa cell lines, T24 and RT‐112, the mechanism of action of 1, 25D3 and cisplatin combination treatment was determined by apoptosis assays, as well as western blot and RT‐PCR. Results: In this study, we determined that low serum 25 hydroxyvitamin D3 (25D3 ) levels was significantly associated with worse response to cisplatin. Pretreating deficient mice with 1, 25D3, reduced tumor volume compared to cisplatin monotherapy. In vitro, 1, 25D3 pretreatment increased the apoptotic response to cisplatin. 1, 25D3 pretreatment increased expression of TAp73 and its pro‐apoptotic targets, in a VDR dependent manner. VDR and its transcriptional targets were induced after 1, 25D3 treatment and further increased after the combination of 1, 25D3 and cisplatin in a TAp73 dependent manner. Conclusions: Our data suggest that VitD deficiency could be a biomarker for poor response to cisplatin, and pretreating with VitD can increase the apoptotic response to cisplatin through VDR and TAp73 signaling crosstalk. Abstract : In this article, we investigated the effects of vitamin D deficiency and sufficiency on the response to cisplatin in bladder cancer. We determined that increased vitamin D status, through either dietary intervention or treating with the active vitamin D metabolite, is associated with a increase in response to cisplatin. Finally, we determined the mechanism of action was due to crosstalk between VDR and TAp73 siganling.